(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
Binaya Climbing is included in the seven summits of Indonesia so that it becomes a tourist destination. To reduce the impact of climbing activities in the conservation area, managers need to limit visitors according to the carrying capacity. This study aims to analyze the carrying capacity of the climbing route by considering the carrying capacity limits so that the attractiveness of the climbing route objects remains sustainable. Data collection was carried out in the Manusela National Park area on the Piliana climbing route and buffer villages that have access to the entrance route to the peak of Mount Binaya via the Piliana Route (South), namely Negeri Piliana. Data collection was carried out in December 2021-January 2022. Primary data and secondary data are needed in this study, the types of data needed in the study are area/distance, biophysical factors, management of the maximum number of visits (quota). Data analysis uses the formula for physical carrying capacity, real carrying capacity and effective carrying capacity. The calculation results of the physical carrying capacity (PCC) of Binaya hiking tourism are 631 people/day, the Real carrying capacity (RCC) is 194 people, and the effective carrying capacity (ECC) is 86 people/day of visits. The results of the analysis show that the Binaya hiking tourism object in receiving visits has not yet exceeded the carrying capacity of the area.